2007
DOI: 10.1186/1749-7922-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative risk scores for the prediction of outcome in elderly people who require emergency surgery

Abstract: Background: The decision on whether to operate on a sick elderly person with an intraabdominal emergency is one of the most difficult in general surgery. A predictive risk-score would be of great value in this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 43 publications
2
73
0
5
Order By: Relevance
“…The ability of health care providers to predict death before surgery is inadequate. 38,39 Decisions to withhold care at the time of presentation may be appropriate for only a small proportion of older adults with advanced frailty or severe comorbidities. Research is needed to develop strategies, such as time-limited trials of care, 40 to minimize the occurrence of high-cost inpatient deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of health care providers to predict death before surgery is inadequate. 38,39 Decisions to withhold care at the time of presentation may be appropriate for only a small proportion of older adults with advanced frailty or severe comorbidities. Research is needed to develop strategies, such as time-limited trials of care, 40 to minimize the occurrence of high-cost inpatient deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk scores for prediction of outcome of peptic ulcer patients have been developed. [13][14][15][16][17][18][19] APACHE score (Acute Physiologic And Chronic Health Evaluation, SAPS (Simplified Acute Physiology Score), MOF Score (Multi Organ Failure) MPI score (Mannheim Peritonitis Score) and other scoring system are cumbersome in difficult to use in all emergency setup and many of them incorporate the intra operative and post-operative status as well.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Seniors are a unique subset of patients with their own problems and vulnerabilities including the cumulative loss of physiologic reserve in almost every organ system, 5 otherwise known as frailty. Recent studies involving patients older than 80 years demonstrated that age and number of comorbidities did not accurately predict poor surgical outcomes, 6 and further studies have suggested that frailty measures are better overall predictors.…”
mentioning
confidence: 99%